Respons Fisiologis Padi (Oryza sativa L.) “Segreng” dan “Menthik Wangi” Terhadap Aplikasi Pupuk Organik Cair dan Dekomposer - Dwi Umi Siswanti; Rega Virgiyana Agustin (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2014)
The background of the community services at Sruni (a part of Wukirsari village) is our concern in degraded land at around of Mount Merapi after eruption 2010. Researcher encourages people of Wukirsari village to self-sufficient in the supply of organic manure for their fields. It is intended to restore the soil nutrients to improve the soil structure. The target of this activity are increasing agricultural productivity, production costs and improving the efficiency of agricultural cultivation. The conclution of this research and community services are biofertilizer producted by Sruni’s people response positively to the growth of rice plants especially in combination between biofertilizer and vegetative and generative decomposers. The combination of biofertilizer and vegetative decomposers gives the effect of increase of leaf chlorophyll content in both varieties of rice plants (Menthik Wangi and Segreng). The combination also gives a striking response to the increase in Activity of Nitrate Reductase (ANR) of the flag of leaf of Segreng plants. Overall ,Researchers have implementing more than 90% of the planned activities in this grant.Keywords: biofertilizer, decomposers, degraded land, Menthik Wangi, rice, Segreng